2013
DOI: 10.3928/23258160-20130715-06
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Progression of Geographic Atrophy in Age-Related Macular Degeneration With SD-OCT En Face Imaging of the Outer Retina

Abstract: BACKGROUND AND OBJECTIVE: Spectral-domain optical coherence tomography (SD-OCT) en face imaging was used to measure the growth of geographic atrophy (GA) and identify baseline anatomic changes in the outer retina in eyes with nonexudative age-related macular degeneration (AMD). PATIENTS AND METHODS: In this prospective study, eyes were imaged using 200 × 200 and 512 × 128 A-scan raster patterns. Outer retinal anatomy was visualized using en face imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 41 publications
2
60
1
1
Order By: Relevance
“…The later occurs in 20% of patients with preexisting clinical hallmarks of this degenerative disease [2,5]. The characteristic appearance of GA results from the loss of the photoreceptor layer, retinal pigment epithelium (RPE), and choriocapillaris [7,8]. In most cases, GA first appears in the parafoveal location and progresses around the fovea and then through the fovea with concomitant loss of central visual acuity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The later occurs in 20% of patients with preexisting clinical hallmarks of this degenerative disease [2,5]. The characteristic appearance of GA results from the loss of the photoreceptor layer, retinal pigment epithelium (RPE), and choriocapillaris [7,8]. In most cases, GA first appears in the parafoveal location and progresses around the fovea and then through the fovea with concomitant loss of central visual acuity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…3 More recently, Spectral-Domain OCT technology with advanced alignment algorithm have adjusted sections to a reference curve, which has allowed layer-by-layer retinal imaging and provided a new investigation tool for a range of retinal disorders. [4][5][6][7][8][9] The foveal microstructure is formed by a dense compaction of cone photoreceptors and their projected axons, which are intertwined with retinal glial Müller cells and follow a centrifugal course towards the inner layers at the edges of the fovea. Retinal glial Müller cells are critical for retinal homeostasis, providing metabolic support to neighboring neural cells, delivering neuroactive substances and retinoids to cones, and recycling waste compounds.…”
Section: Introductionmentioning
confidence: 99%
“…To perform such analyses in future en face SD-OCT images, derived from slabs encompassing the outer retinal bands will be helpful. Approaches for slab generation may be parallel to those used by Nunes et al 21 and Niu et al 25 The latter study presented a predictive model for local GA progression that was based on the thicknesses of various retinal layers and local reflectivity values. Remarkably, in that model-though developed only on a limited number of eyesthe thickness of the RPE-BM complex was one important predictor for atrophy progressions.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The border zone of atrophy represents the area where pathologic processes promote atrophy progression and has, therefore, recently received major attention. [16][17][18][19][20][21] Brar et al 19 originally identified two distinct types of atrophy border: type 1 (also termed 'regular' according to Fleckenstein et al, 18 Fig. 1A) shows smooth margins and no alterations of the outer retina while type 2 (also termed 'irregular', 18 Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation